Heterogeneous 2D/3D Tin‐Halides Perovskite Solar Cells with Certified Conversion Efficiency Breaking 14 - Yu, Bin‐Bin; Chen, Zhenhua; Zhu, Yudong; Wang, Yiyu; Han, Bing; Chen, Guocong; Zhang, Xusheng; Du, Zheng; He, Zhubing (Advanced materials (Weinheim), 2021)
As the most promising lead‐free one, tin‐halides based perovskite solar cells still suffer from the severe bulk‐defect due to the easy oxidation of tin from divalent to tetravalent. Here, a general and effective strategy is delivered to modulate the microstructure of 2D/3D heterogeneous tin‐perovskite absorber films by substituting FAI with FPEABr in FASnI3. The introduction of 2D phase can induce highly oriented growth of 3D FASnI3 and it is revealed in the optimal 2D/3D film that 2D phase embraces 3D grains and locates at the surfaces and grain boundaries. The FPEA+ based 2D tin‐perovskite capping layer can offer a reducing atmosphere for vulnerable 3D FASnI3 grains. The unique microstructure effectively suppresses the well‐known oxidation from Sn2+ to Sn4+, as well as decreasing defect density, which leads to a remarkable enhanced device performance from 9.38% to 14.81% in conversion efficiency. The certified conversion efficiency of 14.03% announces a new record and moves a remarkable step from the last one (12.4%). Besides of this breakthrough, this work definitely paves a new way to fabricate high‐quality tin‐perovskite absorber film by constructing effective 2D/3D microstructures. A general and effective strategy is delivered to modulate the 2D/3D microstructure of tin‐perovskite films by introduction of a 2D phase with the function of FPEABr, which induces high‐orientation growth of 3D FASnI3 by embracing the 3D grains at their surfaces and boundaries. That leads to a breakthrough of device performance of 14.81% in power conversion efficiency, along with 14.03% certified.